Comparative Price and the Design of Effective Product Communications. (September 2016) - Allard, Thomas; Griffin, Dale
The authors propose a model relating a product's comparative price to the construal level of its associated communications and show how perceived expensiveness shapes consumers' response to the wording of marketing communications. A series of six studies shows that for both absolute low- and high-cost product categories, comparatively expensive (inexpensive) products are preferred when accompanied by high-construal (low-construal) messages, due to the conceptual fluency of the "match" between price-induced psychological distance and construal level. The model provides novel implications for designing effective marketing communications: comparatively expensive versions of objectively low-priced products (e.g., an expensive chocolate truffle) are best promoted through more abstract slogans, whereas comparatively affordable versions of objectively high-priced products (e.g., an inexpensive diamond pendant) are best promoted using more concrete slogans. By emphasizing the link between comparative price and the matching level of construal, the authors contribute to a richer view of the interplay between price and product communication in marketing.